DNA mediated transistors based on multi-valued logic - Arjun Kudva. (2013)
Multi-valued logic systems are domains in which logical operations, such as negations, conjunctions and disjunctions are performed on inputs that can take more than two truth-values. While current computing devices perform operations based on Boolean or two-valued logic using semiconductor-based circuitry, there is potential for deoxyribonucleic acid (DNA) to be used as a medium for developing a multi-valued logic system on which logical operations can be done.